Исследование осевых сил крупной волновой передачи - Стрельников, Виктор Никитович (НТУ "ХПИ", 2017)
Представлены результаты экспериментальных исследований осевых сил крупной волновой зубчатой передачи. Измерение осевых сил выполнялось методом тензометрии на гибком колесе и генераторе волн одновременно. При сопоставлении данных экспериментальных исследований и теоретических расчетов, получена удовлетворительная сходимость результатов.

Results of experimental researches of axial forces of a large wave gear are presented. Measurement of axial forces was executed by a tensometry method on a flexible gear and the generator of waves simultaneously. By comparison of the given experimental researches and theoretical calculations, satisfactory convergence of results is received. Experimental studies were conducted on industrial designs wave reducers actuators tilt the mobile mixer load capacity 600 tons of molten metal and ore mill volume 160 m³, weighing 220 tons of ore to be loaded.
Research of axial forces of large wave transmission
Keywords: гибкое колесо; генератор волн; тензорезистор; зубчатая передача; flexible gear; generator of waves; resistive-strain sensor